Hubungan Pengetahuan Ibu dengan Kelengkapan Imunisasi Dasar di Wilayah Kerja Puskesmas Tumbang Manjul - yuliarti yayu; Yunita Anggriani (STIKes Payung Negeri Pekanbaru, 2023)
Background: Immunization is an effort to improve health status by providing immunity against various diseases that can be prevented by immunization (PD3I). The decline in basic immunization coverage is due to the availability of several vaccines.Parental knowledge is an important factor in supporting the growth and development of children, especially in carrying out immunizations.Research purposes :Knowing the relationship between mother's knowledge and completeness of basic immunization in the Working Area of ​​the Tumbang Manjul Health Center in 2023. Research Methods: The design of this study was a correlation analysis study. The research approach uses cross sectional. The population in this study were mothers who had babies aged 1 year as many as 35. The instrument used was a questionnaire. Data analysis used the chi-square test. . Results: The results showed that most of the mothers of babies had good knowledge of basic immunization of babies, most of the mothers gave complete immunizations to their babies. Conclusion: there is a relationship between mother's knowledge about basic immunization and completeness of basic immunization for babies at the Tumbang Manjul Health Center in 2023 (p=0.000; X2=25.014).